Miejsce liturgii w dialogu ekumenicznym w świetle adhortacji apostolskiej Ecclesia in Medio Oriente (EIMO) - Potoczny, Mateusz (Studia Oecumenica, 2012)
'To be, or not to be' for Christians in Middle East where two thousand years ago our faith was born, requires, today even more significantly than in the past, ecumenical unity of the Churches. In the Apostolic Exhortation ìEcclesia in Medio Orienteî, signed by the Pope Benedict XVI in Harissa on September 14th 2012, we read: ìThe urgency of the present hour and the injustice of so many tragic situations invite us to reread the First Letter of Peter and to join in bearing witness to Christ who died and rose againî (EiMO 95). The way to the desired communion will be effective only when the Churches decide to turn back ad fontem, to the true image of the primitive community of the Lord's disciples. Recalling St. Luke's text about the community of the newly converted believers (Acts 2:42), the Pope rediscovered for the Churches in the Middle East the four pillars of modern ecumenism. Particular significance among them seems to be the liturgical life of the believers. Recalling that for the Churches in the Middle East the Liturgy always ìhas been an essential element in the spiritual unity and communion of the faithfulî (EiMO 75), Pope Benedict XVI points to some elements where ecumenical significance may be important to build this unity. Within the article, the author focused on the liturgical life of the Christian communities (especially the sacramental life) and their ecumenical significance. Reading the EiMO we can confidently say that the liturgy of the Church plays a very important role in the modern ecumenical dialogue, and should therefore be understood not only as the future fullness of the unity but has to be considered as the starting point of the ecumenical dialogue.